Strategic Adaptation to Core Tax Administration System (CTAS): A Scenario Planning Analysis - Panji Agung Nugroho (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Indonesia has introduced Core Tax Administration System (CTAS) as a foundation of its tax reform program in order to change tax administration with automation and integration. The subject research is PT Archroma Indonesia, a multinational chemical specialties manufacturing company. SWOT analysis shows that company’s strong IT infrastructure backed by IT team, provides significant strengths in CTAS adaptation. In other side, weaknesses like insufficient Coretax’s training, financial impact from system changes, and limited human resources hinder adaptation initiatives. CTAS’s capacity to combine tax administration procedures, automate reporting, and reduce redundancy creates opportunities. In this case, threats consist of system downtime, operational disruptive, cybersecurity weaknesses, and regulatory uncertainty. Scenario planning investigates more the interaction of two important uncertainties: government system reliability and regulatory stability. The research finds that reducing Coretax risk depends on strategic agility, improved cross-department communication, and collaborative involvement of stakeholders. Early warning systems based on leading indicators such as system uptime and stable regulatory which allow company for quick adjustment in compliance strategies.